Single-molecule fluorescence microscopy studies of DNA-surface interactions on chemically graded organosilane surfaces - Li, Zi (Kansas State University, 2018)
This dissertation describes the application of wide-field single-molecule fluorescence microscopy techniques to investigations of DNA-surface interactions on chemically graded organosilane surfaces. The adsorption and desorption behaviors of double-stranded (ds) plasmid DNA along the amino-trimethoxysilane and octyl-trichlorosilane gradients were explored as a function of solution pH, solution ionic strength and surface properties. The results provide an improved fundamental understanding of DNA interactions with different surfaces and are certain to aid in the development and advancement of DNA-based biological and biomedical devices. Three distinct experiments were performed in completion of the work for this dissertation. In the first study, total internal reflection fluorescence (TIRF) microscopy was employed to study DNA interactions with aminosilane gradient surfaces under relatively acidic and basic environments. Electrical potentials were applied to assist DNA adsorption and desorption. The single-molecule data clearly showed that DNA capture and release was achieved on the monolayer and submonolayer coated regions of the aminosilane gradient surface under relatively basic pH conditions, with the help of an electrical potential. Meanwhile, DNA adsorption was found to be quasi-reversible on the multilayers at the high aminosilane end of the gradient in the relatively acidic solution. The results of these studies demonstrate the importance of manipulating the electrostatic interactions of DNA with charged surfaces in order to achieve DNA capture and release. The fundamental knowledge of the DNA-surface interactions gained in these studies will be helpful in diverse fields ranging from the layer-by-layer assembly of polyelectrolyte-based thin films to the selective electronic sensing of charged biomolecules. In the second study, the local dielectric properties of the least polar environments in dsDNA were assessed by using the solvatochromic dye, nile red, as a polarity-sensitive probe. TIRF spectroscopic imaging methods were employed in these studies. Although the dielectric constant within the least polar regions of dsDNA was previously predicted by theoretical and computational methods, no experimental measurements of its value had been reported to date. The results provide important knowledge of the factors governing the polarity of DNA microenvironments to which intercalators bind, and provide vital experimental support for the values determined in computational studies. In the third study, TIRF microscopy and single molecule tracking methods were employed to study DNA interactions with an opposed two-component C8-silane and aminosilane gradient surface as a function of solution pH. The mobility of surface-adsorbed DNA molecules was explored and quantified in these studies. The preliminary results further demonstrated the importance of electrostatic interactions over hydrophobic interactions in governing the adsorption of DNA to surfaces. The mobility of surface-adsorbed DNA was found to be largely independent of position along the two-component gradient. These studies were originally undertaken as a route to observation of cooperative effects that are believed to govern DNA-surface binding. Unfortunately, no clear evidence of cooperative effects was observed at the mixed regions of the two-component gradient surface.
Keywords: DNA-surface interactions; Wide-field fluorescence microscopy; Organosilane gradient surfaces; Vapor phase deposition; Single molecule studies; Dielectric constant inside DNA